Potentials of OME/diesel blends for stationary power production – Improving emission characteristics of a diesel CHP unit. (5th May 2019) - Popp, T.; Lechner, R.; Becker, M.; Hebauer, M.; O'Connell, N.; Brautsch, M.
Highlights: No performance and efficiency drawbacks were observed when applying OME blends. OME/diesel blends significantly mitigated PM-NOx trade-off. Particle number and size decreased significantly with rising OME content in blend. EGR could become a feasible option for stationary engines. Abstract: Polyoxymethylene dimethyl ethers (OME) with the chemical structure H3 CO[-CH2 -O-]n CH3 are a promising alternative fuel for improving emissions characteristics of internal combustion engines and can be produced from renewable sources. Especially the PM-NOx trade-off of diesel engines is known to be effectively mitigated by blending OME with diesel. Recent investigations concentrate on the utilization OME fuels in mobile applications. However, these fuels could also be of interest for stationary engines used in gensets and combined heat and power units (CHP). In the present paper we examine the use of OME2-6/diesel blends up to 50% in a CHP unit in practical operation equipped with a heavy-duty six-cylinder engine, applying different load conditions and engine settings, including Exhaust Gas Recirculation (EGR) and the adjustment of injection timings. No negative effects on the performance and efficiency of the engine were observed with the OME blends. Particulate Matter (PM) and Particle Number (PN) decreased significantly with increasing content of OME in the blend, especially when EGR was applied. The Particle Number Size Distribution (PNSD) showed a trend towards smaller particle sizes. NOx rose slightly in direct comparison, but this was by far overcompensated by the reduction achieved through EGR. The results indicate that OME fuels in combination with EGR could become a feasible option for emission reduction in diesel gensets and CHP units due to the very low particle emissions, which mitigate the risk of EGR cooler fouling.